Cloud-Based Learning Platforms and Their Impact on English Writing Skills in Rural Schools - Olivia Green; Thomas Mitchell; Amine Ali (Yayasan Adra Karima Hubbi, 2025)
Background. In rural Indonesian schools, where access to qualified English teachers and adequate learning resources is often limited, these platforms provide a potential solution to reduce the urban rural education gap, particularly in the development of writing skills. Purpose. This study aimed to investigate the impact of cloud-based learning platforms on students’ English writing skills in rural secondary schools. It focused on examining how digital collaboration, feedback mechanisms, and self-paced learning influence writing performance and learner engagement. Method. A mixed-method research design was employed involving 100 students from three rural secondary schools in Indonesia. Participants took part in a 10-week instructional intervention using cloud-based platforms, namely Google Classroom and Microsoft OneNote. Results. The findings indicated a significant improvement in students’ English writing performance after the intervention (p < .05), particularly in text organization, vocabulary use, and grammatical accuracy. Qualitative analysis revealed that cloud-based platforms increased learner motivation, promoted peer collaboration, and enabled timely and effective teacher feedback despite existing infrastructural limitations. Conclusion. The study concludes that cloud-based learning platforms effectively support the development of English writing skills in rural educational contexts.